Experienced workload, stress, and coping among professional students in higher music education : An explanatory mixed methods study in Finland and the United Kingdom - Jääskeläinen, Tuula; López-Íñiguez, Guadalupe; Lehikoinen, Kai (SAGE, 2022)
Proactive coping styles may help students deal with their study workload and stress in healthier ways. In this explanatory mixed methods study, data were gathered among professional students in higher music education in Finland and the United Kingdom about their experiences of workload, stress, and proactive coping. Bivariate analyses were used to explore prevalence of study workload, stress, and seven proactive coping styles among genders, levels of degree, genre groups, and study programs, and investigate whether stress is predicted by study workload and proactive coping styles. Music students’ lived experiences were analyzed to find the determinants of their workload, stress, and coping. Results indicate significant differences between genders and study programs and specific concerns for music students, such as working alongside studying and physical and psychological problems. Higher music education institutions can utilize this evidence to better support music students in their studies and professional careers.
Keywords: musiikki; musiikkikasvatus; korkeakouluopiskelu; opiskelijat; stressi; korkeakoulut